Relationship Levels Of Emergency (Triase) With Anxiety Level Of The Patient's Family In The Emergency Installation Of Ulin Hospital, Banjarmasin - Yunita, Yunita; Yulyanti, Yulyanti; Tajaruddin, Muhammad; Aufa, Naimatul (Jurnal EduHealth, 2022)
Anxiety is an emotional response to an assessment that describes a state of worry, anxiety, fear, and restlessness accompanied by various physical complaints. During the treatment process, anxiety is felt by a patient and can also be experienced by the patient's family. The patient's family is one of the top decision-makers when the patient is in an emergency or critical condition and must be given immediate treatment. The study aimed to determine the relationship between the Emergency Level (Triage) and the Anxiety Level of the Patient's Family. The research design used is association analytic with a cross-sectional approach. The research was carried out at the Emergency Installation of Ulin Hospital Banjarmasin. The sample of this study is the patient's family with consecutive sampling technique, obtained a sample of 30 respondents. Data was collected using the HARS questionnaire. Spearman's rho statistical test analyzed data. The results showed that as many as 12 respondents (40%) entered the yellow Triage, and as many as 9 respondents (30%) had moderate levels of anxiety. The results of the bivariate test obtained p value = 0.000, which means that there is a relationship between the level of emergency (triage) and the level of anxiety of the patient's family with a correlation coefficient of -0.748 which means the higher the respondent's emergency, the higher the respondent's level of anxiety. This negative result occurs because the coding for the first emergency level is Red Triage, while the code for the first level of anxiety is not anxious. There is a significant relationship; this can be caused because when there are respondents who enter the red Triage, the family assumes that the patient's hope for recovery is getting smaller, so that family anxiety increases. This study concludes that the higher the level of emergency (Triage) of the patient, the higher the level of anxiety of the patient's family. Recommendations for hospitals, especially in the Emergency Room, are expected further to improve communication between health workers and patient families. To reduce the possibility of anxiety in the family